2014
DOI: 10.1097/gme.0b013e3182a46a3e
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of complementary and alternative medicine use in menopause

Abstract: The findings of this critical review provide insights for those practicing and managing health care in this area of women's health. Healthcare providers should prepare to inform menopausal women about all treatment options, including CAM, and should be aware of the possible adverse effects of CAM and potential interactions between CAM and conventional medicine among women in menopause who are under their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 90 publications
(201 reference statements)
0
10
0
Order By: Relevance
“…The systematic review analyses the contemporary scholarship using an established approach developed for a number of health research topics. [16][17][18] search strategy Peer-reviewed articles reporting on TCAM use in Sub-Saharan Africa were searched using the following databases: Cumulative Index to Nursing and Allied Health Literature, Allied and Complementary Medicine Database, Scopus, ProQuest, Medline, PubMed, African Journals Online, Embase and Google Scholar. Hand searching in the bibliography of relevant articles was also employed to help ensure the capture of all relevant peer-reviewed literature.…”
Section: Methodology Research Designmentioning
confidence: 99%
“…The systematic review analyses the contemporary scholarship using an established approach developed for a number of health research topics. [16][17][18] search strategy Peer-reviewed articles reporting on TCAM use in Sub-Saharan Africa were searched using the following databases: Cumulative Index to Nursing and Allied Health Literature, Allied and Complementary Medicine Database, Scopus, ProQuest, Medline, PubMed, African Journals Online, Embase and Google Scholar. Hand searching in the bibliography of relevant articles was also employed to help ensure the capture of all relevant peer-reviewed literature.…”
Section: Methodology Research Designmentioning
confidence: 99%
“…However, the Women’s Health Initiative study conducted in 2002 indicated that MHT increases cardiovascular risk, and that, overall, its harm exceeds its benefits [ 15 ]. This sparked a great deal of concern over effective non-hormone therapies, including prescription and nonprescription therapies [ 16 , 17 ]. Prescription therapies, prime examples of which are plant-based therapies and herbal medicinal products, have been systematically reviewed; they produce a modest reduction in the frequency of vaginal dryness and hot flashes but no significant reduction in night sweats [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, a spread of non-hormonal therapies is observed: data from different surveys show that around 30%–80% of women with HFs employ non-hormonal treatments [1113]. The prevalence of complementary and alternative medicine (CAM) therapies is increasing as showed by the Study of Women’s Health Across the Nation, being 48.5% in 2002 and 80% in 2008 [11].…”
Section: Introductionmentioning
confidence: 99%